PERSEPSI PENYULUH TERHADAP STRATEGI KOMUNIKASI DALAM PEMANFATAN MEDIA INFORMASI DI ERA DIGITAL DI KABUPATEN TASIKMALAYA - Dona Setia Umbara; Lies Sulistoyowati; Trisna Insan Noor; Iwan Setiawan (Universitas Galuh Ciamis, 2021)
The rapid development of digital technology has many media that can be used so that it has brought various changes to both extension workers and farmers. Digital media in the form of communication media that can be used today are virtual world media or internet media. Agricultural instructors have an important role in conveying information and are required to be able to use internet media to support their main tasks and functions as agricultural extension workers. In carrying out communication activities in the diffusion of innovation. The purpose of this study is to describe the perception of extension workers in the use of digital technology in the delivery of counseling. The study used a survey method with a sampling technique using random sampling consisting of 60 extension workers. Data analysis to measure the instructor's perception of the instructor's communication strategy in the use of digital media was done by calculating the score. The results showed that the communication strategy used by extension workers in delivering counseling to farmers could be applied so that farmers could carry out intensive communication activities using digital media more efficiently and effectively in delivering recommendations suggested in farming. Extension workers have a positive perception of communication strategies in utilizing information as seen from communication techniques, communication channels, communication messages and internet usage. Extension activities can be delivered anytime and anywhere, use information technology, can use existing sources on the internet to then make extension materials, can connect in real time using video conference or video streaming, have the ability to integrate various elements of text media, graphics , audio, and video in providing counseling to farmers.